Hukum Jual Beli Borongan Buah Manga Dari Pohon Perspektif Hukum Islam Dan ‘Urf (Studi Kasus Di Kota Probolinggo) - Billah, Ana; Romli, Ahmad Syaifuddin (LPPM UNU BLITAR, 2024)
Buying and selling is an activity that is often carried out by humans everywhere. Sale and purchase is a contract in which the seller gives ownership of his goods to the buyer, the goods are accepted by the buyer, and money is given to the seller in return. Moreover, wholesale buying and selling is often applied in Probolinggo City. Wholesale buying and selling is often applied in buying mangoes that are still on the tree and without being weighed. The method used is empirical. By looking at the phenomena that occur in the field. From the results of the study, it is said that it is permissible to buy and sell wholesale according to Islam. Because both parties are equally willing with the proposed offer. Even without weighing first. If it is agreed, it will continue in the process of transferring property rights. Meanwhile, in terms of urf, wholesale buying and selling has become a habit practiced in the Probolinggo community. So that there is no deviation from the custom in the wholesale sale and purchase transaction of mangoes. Keywords : Law of Sale and Purchase, 'Urf , Wholesale